High-color-purity and efficient solution-processable blue phosphorescent light-emitting diodes with Pt(ii) complexes featuring 3ππ* transitions. (19th September 2019) - Ma, Huili; Shen, Kang; Wu, Yipei; Xia, Fang; Yu, Feiling; Sun, Zhengyi; Qian, Chunyue; Peng, Qiming; Zhang, Hong-Hai; You, Cong; Xie, Guohua; Hang, Xiao-Chun; et al.
Abstract : A series of Pt(ii ) complexes with narrow emission spectra were systematically investigated and Pt(ppzOczpy-4m), rationally designed with predominantly 3 LC( 3 ππ*) character in T1, was fabricated into efficient blue OLEDs via a solution process. Abstract : A series of tetradentate Pt(ii ) complexes featuring narrow emission spectra have been systematically exploited. The lowest excited states of the molecules can experience delocalized spin transitions during intersystem crossing, leading to local 3 ππ* transitions with narrow emission spectra. We found that the photophysical properties expressed by decay lifetimes, radiative decay rates and full width at half maximum (FWHM) values in the spectra correspond to the configurational ratio of the local 3 ππ* components, which could be regulated upon structure modification and environmental confinement. Photoluminescent data analysis with zero-field splitting of less than 14 cm −1 stresses the important role of the 3 ππ* transitions. Pt(ppzOczpy-4m), simply modified by adding methyl to a Pt(ppzOczpy) frame, gives a 92% photoluminescent yield in dichloromethane and a narrow phosphorescent emission spectrum with a FWHM of 25 nm in the blue region. In application, solution processed deep-blue organic light-emitting devices based on Pt(ppzOczpy-4m) achieve a high maximum external quantum efficiency (EQEmax ) of 19.5% with Commission Internationale de L'Eclairage (CIE) coordinates of (0.159, 0.166) and 11.9% EQEmax with optimal CIE coordinates of (0.154, 0.130).